Development of Quick Cooking Dalia utilizing Sprouted Wheat - D.*, Mridula; Sharma, Monika; Manikantan, M.R.; Gupta, R.K. (Journal of Agricultural Engineering, 2014)
Present study was carried out to develop quick cooking wheat dalia using wheat sprouted for 36 and 48 h, dried at 50oC, followed by milling. Recovery of dalia (particle size 1.41 to 2 mm) from unsprouted, 36 h and 48 h sprouted wheat was 75.1, 74.41 and 73.8%, respectively. Sprouting and particle size affected the physical properties and cooking quality of wheat dalia. Rehydration ratio and solid loss in cooking water of different dalia samples ranged from 3.15 to 3.39 and 10.26 to 13.34%, respectively. Cooking time of dalia samples (3.2 to 7.38 min) was reduced due to sprouting, but sprouting did not affect the sensory characteristics. Overall sensory acceptability scores for dalia samples ranged from 7.69 to 7.98 with better acceptability for dalia prepared from 36 h sprouted wheat. Protein, fat, minerals, crude fibre, calories, iron and calcium content in this dalia sample were 10.32%, 1.33%, 1.48%, 3.33%, 359 kcal, 1.18 and 44.67 mg/100 g, respectively. In vitro protein digestibility of dalia from unsprouted, 36 and 48 h sprouted wheat was 47.46, 62.72 and 70.06%, respectively. In view of good acceptability, lesser cooking and sprouting time, quick cooking wheat dalia may be prepared from 36 h sprouted wheat, which also stored well for 90 days at room temperature.